-6+8k=4(1+4k)-6k

Simple and best practice solution for -6+8k=4(1+4k)-6k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6+8k=4(1+4k)-6k equation:


Simplifying
-6 + 8k = 4(1 + 4k) + -6k
-6 + 8k = (1 * 4 + 4k * 4) + -6k
-6 + 8k = (4 + 16k) + -6k

Combine like terms: 16k + -6k = 10k
-6 + 8k = 4 + 10k

Solving
-6 + 8k = 4 + 10k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-10k' to each side of the equation.
-6 + 8k + -10k = 4 + 10k + -10k

Combine like terms: 8k + -10k = -2k
-6 + -2k = 4 + 10k + -10k

Combine like terms: 10k + -10k = 0
-6 + -2k = 4 + 0
-6 + -2k = 4

Add '6' to each side of the equation.
-6 + 6 + -2k = 4 + 6

Combine like terms: -6 + 6 = 0
0 + -2k = 4 + 6
-2k = 4 + 6

Combine like terms: 4 + 6 = 10
-2k = 10

Divide each side by '-2'.
k = -5

Simplifying
k = -5

See similar equations:

| 7-15t=5s-3 | | 4x+-15=17+-4x | | w*W+16=8w | | 25=7+3k-n | | 11x+136=180 | | 7x-10=4x+10 | | 13x+77=90 | | x^2+2ix+1=0 | | f(x)=9x^2-16 | | 5x-4y=10findy | | 65+2x-5=180 | | 3x(4-8+3)= | | 24ax-(1+a^2)x^2=0 | | 2w-8y=zy | | 3.2e-08=x | | n-8+9=1-4n | | 2(x-3)=.5(4x-12) | | -11j-6+j=30 | | (3x+1/2)+(7x-41/2)= | | 2x^2+4x-5-5x^2+4x+1= | | 2X(X+4)=14 | | 13x+51=90 | | 5=6v | | f(x)=lx-1l+4 | | 5x+5=8x-13 | | -14-3n=5n-6n | | 5.61-8.94=3.76m+4.86 | | 5(w+2)=4(w+1) | | 13x+167=180 | | 6x-5x+4=-6 | | w=3(x+y+z)y | | v-16=-6 |

Equations solver categories